2004
DOI: 10.1128/mcb.24.1.46-57.2004
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Processing of the WSC Family and Mid2p Cell Surface Sensors Results in Cell Death of Saccharomyces cerevisiae O-Mannosylation Mutants

Abstract: Protein O mannosylation is a crucial protein modification in uni-and multicellular eukaryotes. In humans, a lack of O-mannosyl glycans causes congenital muscular dystrophies that are associated with brain abnormalities. In yeast, protein O mannosylation is vital; however, it is not known why impaired O mannosylation results in cell death. To address this question, we analyzed the conditionally lethal Saccharomyces cerevisiae protein O-mannosyltransferase pmt2 pmt4⌬ mutant. We found that pmt2 pmt4⌬ cells lyse a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
131
0
10

Year Published

2004
2004
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(148 citation statements)
references
References 63 publications
7
131
0
10
Order By: Relevance
“…The latter is noteworthy, since the PKC1-dependent cell wall integrity pathway is defective in the O-glycosylation mutants impaired in the activity of protein-O-mannosyl transferases (PMTs) (Strahl-Bolsinger et al, 1999). In these mutants, Mpk1p (Slt2) phosphorylation could be restored in part by overexpression of proteins acting upstream of the pathway, such as the cell wall sensors from the Wsc family and Mid2p (Lommel et al, 2004). Under our experimental conditions, however, despite the general defect of glycosylation ascribed to sec59-1 or dpm1-6 mutants, the Mpk1/Slt2p phosphorylation is still observed.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is noteworthy, since the PKC1-dependent cell wall integrity pathway is defective in the O-glycosylation mutants impaired in the activity of protein-O-mannosyl transferases (PMTs) (Strahl-Bolsinger et al, 1999). In these mutants, Mpk1p (Slt2) phosphorylation could be restored in part by overexpression of proteins acting upstream of the pathway, such as the cell wall sensors from the Wsc family and Mid2p (Lommel et al, 2004). Under our experimental conditions, however, despite the general defect of glycosylation ascribed to sec59-1 or dpm1-6 mutants, the Mpk1/Slt2p phosphorylation is still observed.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation could be the alteration of the sensors that activate the Mkc1p pathway. Recently, in S. cerevisiae, it has been shown that the incorrect Omannosylation of the Wsc1p, Wsc2p and Mid2p receptors in pmt2D pmt4D mutants prevents the activation of Slt2p upon exposure to elevated temperature (Lommel et al, 2004). In C. albicans, Hog1p might control the expression of the proteins involved in glycosylation of the receptors that activate the Mkc1p MAP kinase pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Wsc1 and Mid2 serve a partially overlapping role in detecting and transmitting cell wall status to Rho1. N-or O-glycans of these two molecules are important for their function (Lommel et al, 2004;Philip & Levin, 2001;Hutzler et al, 2008). Upon environmental stimuli or cell wall stress, Rho1 is activated, which then activates downstream effectors such as the Pkc1-MAP kinase cascade, b-1,3-glucan synthase and Bni1/ SepA formin protein (Walther & Wendland, 2003;Longtine & Bi, 2003;Guest et al, 2004).…”
Section: Discussionmentioning
confidence: 99%